Phenolic compounds from Aquilaria microcarpa stem bark - Alfinda Novi Kristanti, .- (University of Chemical Technology and Metallurgy, Sofia, Bulgaria, 2017)
This paper reports a study of secondary metabolites contained in Aquilaria microcarpa, a species belonging to Thymelaceae. This species has not been investigated so far. Aquilaria microcarpa is one of Aquilaria species that grows in Indonesia. The sample plant used is taken from east Kalimantan. Extraction of stem bark is done using methanol. Two phenolic compounds, namely 5,3’,4’-trihydroxy-7-methoxyflavon or known as 3’-hydroxy genkwanin and 6-hydroxy-2-(2-phenylethyl)chromone are isolated and identified. The chemical structure of these compounds is determined based on spectroscopic data, as well as HR-ESI-MS and NMR spectra. Both compounds were reported previously but they were extracted from another species of Aquilaria.